2015
DOI: 10.17221/8077-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of source of methionine in broken rice-soybean diet on production performance, blood chemistry, and fermentation characteristics in weaned pigs

Abstract: ABSTRACT:This study was conducted to compare the effect of source of methionine (Met) in broken ricesoybean diet on performance, blood biochemistry, and fermentation characteristics in weaned pigs. Forty-eight male crossbreed pigs (BW 11 ± 0.1 kg) were randomly allocated to three groups with four replications in a completely randomized design. The experimental diets were: (1) basal diet without methionine (Control; total sulfur amino acids (TSAA) 0.60%); (2) basal diet supplemented with dl-methionine (DLM) (TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…The lower feed intake may explain the decrease in growth promotion of 0.24% group. Although the relative bioefficacy of DL-MHA to DL-Met has been reported to be lower than 88% ( Kim et al, 2006 ; Dilger and Baker, 2008 ), Bunchasak et al (2014) and Krutthai et al (2015) showed that 88% bioefficacy may be an acceptable with regard to SAA requirement. Therefore, based on 88% bioefficacy (w/w) compared to DL-Met, supplementation of DL-MHA at 0.15% and 0.24% of diet result in SID SAA:Lys ratio at 61% and 69%, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The lower feed intake may explain the decrease in growth promotion of 0.24% group. Although the relative bioefficacy of DL-MHA to DL-Met has been reported to be lower than 88% ( Kim et al, 2006 ; Dilger and Baker, 2008 ), Bunchasak et al (2014) and Krutthai et al (2015) showed that 88% bioefficacy may be an acceptable with regard to SAA requirement. Therefore, based on 88% bioefficacy (w/w) compared to DL-Met, supplementation of DL-MHA at 0.15% and 0.24% of diet result in SID SAA:Lys ratio at 61% and 69%, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…(1992) who reported that supplementation of organic acids in diet did not change the pH in the gut. Recently, Krutthai et al (2015) also reported low potentiality of acidifying by DL-MHA throughout gastrointestinal tract of piglets. Since supplemental DL-MHA induces dietary acidity ( Krutthai et al, 2015 ), the presence of an acidic diet may affect a low pH in stomach, leading to a negative feedback mechanism that inhibits HCl secretion ( Yen, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples of caecum digesta were centrifuged for 10 min at 14,000xg at 4ºC and the supernatants were sampled to determine the lactic acid and short-chain fatty acids (SCFAs) concentrations. The concentrations of lactic acid and SCFAs were determined under the following conditions using a HPLC (Krutthai et al 2015).…”
Section: Analysis Of Lactic Acid and Scfas Concentrations In The Caecummentioning
confidence: 99%